Pengaruh ESG, Board Gender Diversity, dan Board Age Diversity Terhadap Kinerja Keuangan pada Perusahaan Sektor Perbankan yang Terdaftar di BEI - Aulia Arifiona; Sri Wahyundaru (Penerbit Jurnal Indonesia, 2026)
Increasing attention to sustainability practices and the demand for greater transparency in corporate governance have encouraged the banking sector to strengthen its non-financial performance as part of its business strategy. In this context, ESG and board characteristics have become important indicators that are believed to influence corporate performance. Based on this condition, this study aims to analyze the effect of Environmental, Social, and Governance (ESG), Board Gender Diversity (BGD), and Board Age Diversity (BAD) on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. This research employs a quantitative approach with multiple linear regression analysis. The sample was determined using a purposive sampling technique, resulting in 17 companies and 50 observations. Financial performance was measured using Return on Equity (ROE), while ESG data and board characteristics were obtained from annual reports and the LSEG Datastream (Refinitiv) database. The results indicate that ESG has a significant positive effect on financial performance, whereas Board Gender Diversity and Board Age Diversity do not have significant effects. These findings highlight that sustainability factors play a more dominant role than demographic characteristics of the board in enhancing the financial performance of banking companies in Indonesia.